1995
DOI: 10.1152/jappl.1995.79.3.795
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal changes in normal and polycythemic high-altitude natives

Abstract: Acute and chronic exposure to high-altitude (HA) hypoxia inhibits the renin-angiotensin-aldosterone system and may modify the release of atrial natriuretic peptide (ANP) in sea-level (SL) natives. In HA natives, the release of these hormones could be influenced by changes in blood volume or pulmonary arterial pressure. Twenty-four men residing in La Paz, Bolivia, at 3,600 m were separated into two groups: one normocythemic (HAN; with hematocrit < 57%; n = 13) and the other polycythemic (HAP; with hematocrit > … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
1
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 0 publications
1
15
1
1
Order By: Relevance
“…It is likely that there would have been a greater sympathetic activation in the more hypoxaemic CMS patients, and this may have contributed to the altered carotid baroreflex function. This hypothesis is supported by the observation that resting noradrenaline and adrenaline levels are greater in CMS patients than in HA normal subjects (Antezena et al 1995), suggesting greater levels of sympathetic activity.…”
Section: Discussionmentioning
confidence: 74%
“…It is likely that there would have been a greater sympathetic activation in the more hypoxaemic CMS patients, and this may have contributed to the altered carotid baroreflex function. This hypothesis is supported by the observation that resting noradrenaline and adrenaline levels are greater in CMS patients than in HA normal subjects (Antezena et al 1995), suggesting greater levels of sympathetic activity.…”
Section: Discussionmentioning
confidence: 74%
“…However, the available information on HPA axis function in Sherpas or other lineages that have adapted to HA living is limited. Previous studies have observed a blunted sympathoneural response to hypobaric hypoxemia in HA natives of Bolivia and the Andes [45,46] and a blunt ACTH and cortisol response to exogenous CRH in HA natives of Andes [47]. Thus, the distinctive physical and physiological characteristics of HA natives are possible explanations for the observed differences in HPA axis and cardiovascular function between Sherpas and trekkers during the trek on the Annapurna circuit.…”
Section: Discussionmentioning
confidence: 92%
“…A number of human and animal studies have shown that high altitude exposure and its associated relative hypoxia induce changes in the hematologic and hemodynamic profiles of adults and fetuses. [1][2][3][4][5][6][7] Human studies showing a decrease in birth weight at high altitude have been performed in Leadville, Colo (altitude, 3100 m) and in Tibet (altitude, 3658 m). [8][9] Reduced birth weight has also been reported at moderately high altitude (Denver, 1600 m) compared with sea level.…”
mentioning
confidence: 99%